An Elusive Prize: Transcutaneous Near InfraRed Spectroscopy (NIRS) Monitoring of the Liver - Guyon, Peter W.; Karamlou, Tara; Ratnayaka, Kanishka; El-Said, Howaida G.; Moore, John W.; Rao, Rohit P. (Frontiers in Pediatrics, 2020)
Introduction: We contend adding hepatic NIRS monitoring to the current dual-site (cerebral-renal) NIRS paradigm will increase the sensitivity for detecting shock in the pediatric cardiovascular intensive care unit (CVICU). The rationale is regional oxygen delivery will change in the splanchnic circulation before changes are seen in the liver or brain. We explored a reliable technique for hepatic NIRS monitoring as a prelude to rigorously testing this hypothesis. This study aimed to validate hepatic NIRS monitoring by comparing hepatic NIRS measurements to direct hepatic vein samples obtained during cardiac catheterization. Method: IRB-approved prospective pilot study of hepatic NIRS monitoring involving 10 patients without liver disease who were already undergoing elective cardiac catheterization. We placed a NIRS monitor on the skin overlying liver during catheterization. Direct measurement of hepatic vein oxygen saturation during the case compared with simultaneous hepatic NIRS measurement. Results: There was no correlation between the Hepatic NIRS values and the directly measured hepatic vein saturation (R=-0.035; P=0.9238). However, the Hepatic NIRS values correlated with the cardiac output (R=0.808; P=0.0047), the systolic arterial blood pressure (R=0.739; P=0.0146), and the diastolic arterial blood pressure (R=0.7548; P=0.0116). Conclusions: Using the technique described, hepatic NIRS does not correlate well with the hepatic vein saturation. Further optimization of the technique might provide a better measurement. Hepatic NIRS does correlate with cardiac output and thus may still provide a valuable additional piece of hemodynamic information when combined with other non-invasive monitoring.